2022
DOI: 10.1021/acsfoodscitech.2c00289
|View full text |Cite
|
Sign up to set email alerts
|

Cellulose Nanocrystals Examined by Atomic Force Microscopy: Applications and Fundamentals

Abstract: Cellulose nanocrystals (CNCs) are nanoscale particles with huge surface areas, excellent mechanical properties, and the ability to develop tunable surface chemistry, thus allowing them to be mixed into a wide range of matrices. Using atomic force microscopy (AFM), we highlight recent developments in the microstructural characterization of CNC particles in various shapes at both particle and organization scales. Considering new uses for CNC suspensions and gels and given the considerable potential of CNC-based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 285 publications
2
6
0
Order By: Relevance
“…The second largest direction was along the hydrogen bonds within the cellulose planes and the smallest modulus obtained was calculated in the stacking direction of cellulose planes with only weak van der Waals interactions. Experimental Young’s moduli for these two directions vary from 8 to 57 GPa, which is also in reasonable agreement with our results [ 26 ]. The calculated bulk modulus for pure cellulose was 17.1 GPa and shear modulus 8.9 GPa.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The second largest direction was along the hydrogen bonds within the cellulose planes and the smallest modulus obtained was calculated in the stacking direction of cellulose planes with only weak van der Waals interactions. Experimental Young’s moduli for these two directions vary from 8 to 57 GPa, which is also in reasonable agreement with our results [ 26 ]. The calculated bulk modulus for pure cellulose was 17.1 GPa and shear modulus 8.9 GPa.…”
Section: Resultssupporting
confidence: 92%
“…As expected, the largest Young’s modulus was obtained along the cellulose chains. The experimental Young’s moduli reported for cellulose vary a lot, but for the fully crystalline case, values larger than 100 GPa and even up to 138 GPa have been reported in the direction of the cellulose chains [ 26 , 27 ]. Our calculated value would be in good agreement with the value of 138 GPa.…”
Section: Resultsmentioning
confidence: 99%
“…6d. However, Convolution of the tip shape in conjunction with the sharp edges of the nanocrystals can make the width of CNCs appear to be much larger than what they truly are [41],…”
Section: Size and Morphology Analysismentioning
confidence: 99%
“…It is known that CNC mechanical properties can vary depending on the source or the method of synthesis [7], [28], [49]. Differences are found not only in the morphology of the particles but also in other characteristics such as thermal stability [50], chemical properties [50], and mechanical properties [41]. For example, a method similar to the one used in this study was performed on a single Tunicate CNC on a Mica substrate using FDS and reported an of 9 GPa with a standard deviation of 2 GPa [47].…”
Section: Mechanical Property Analysismentioning
confidence: 99%
“…The micro- and nanostructure of a polymer material significantly influences the macroscale physical properties, including toughness, mechanical strength, ductility, wear resistance, etc . AFM introduces students to the characterization of polymer materials at the nanoscale level as it measures a range of material characteristics such as surface morphology, roughness, elasticity, stiffness, and surface adhesion. For instance, in previous reports, students were introduced to nanoscale-resolution topography imaging for surface characterization of various materials, including polyvinylpyrrolidone films, silver wires, gold nanoparticles, and dewaxed tomato cuticles . Force curves obtained by AFM nanoindentation were used to familiarize students with quantifying elastomer stiffness, examining the connection between surface functionalization and adhesion forces, and determining the attractive–repulsive forces of optical storage discs .…”
Section: Introductionmentioning
confidence: 99%